Bibliometric Study of Sexual Self-Care Education: A Review of Research Conducted Over the Past 30 Years - Hojjat, Hameedeh; Samavi, Seyed Abdulvahab; Mousapour, Nematollah; Ahmadi, Fatemeh Zahra (Mental Health and Lifestyle Journal, 2026)
The aim of this study is to identify temporal developments, geographical expansion, influential contributors, and conceptual growth in the field of sexual self-care. This research applies a bibliometric analysis to studies published on sexual self-care. All scientific outputs indexed in the Scopus database between 1993 and 2023 were considered the statistical population of this study. The data were analyzed using VOSviewer software, version 1.6. By searching relevant keywords in Scopus, 1,186 documents referencing sexual self-care in their titles, keywords, or abstracts were identified. The highest number of publications in this field was indexed in 2023. White was recognized as the most prolific author with 12 articles, and the article by Wolf et al. (2009) was identified as the most frequently cited. The United States and the United Kingdom were also recognized as among the oldest and most highly cited countries in this area.